2024
DOI: 10.1186/s12864-023-09813-4
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and expression analysis of the ADH gene family under diverse stresses in tobacco (Nicotiana tabacum L.)

Ruiqi Wang,
Chaofan Du,
Gang Gu
et al.

Abstract: Background Alcohol dehydrogenases (ADHs) are the crucial enzymes that can convert ethanol into acetaldehyde. In tobacco, members of ADH gene family are involved in various stresses tolerance reactions, lipid metabolism and pathways related to plant development. It will be of great application significance to analyze the ADH gene family and expression profile under various stresses in tobacco. Results A total of 53 ADH genes were identified in tobac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Mechanisms such as polyploidization and region-specific gene duplication, including tandem repeats and segmental repeats, have been considered as important mechanisms for the expansion of plant gene families [ 29 , 30 ]. This study revealed the presence of homologous gene clusters and collinear gene pairs identified in both tobacco (1 homologous gene cluster and 6 collinear gene pairs) and potato (4 homologous gene clusters and 7 collinear gene pairs), indicating that replication events were the main source of DIR gene family expansion in these species [ 29 , 31 ]. It is worth noting that the incomplete genomic assembly of tobacco, with nearly half of the NtDIR genes located on scaffolds, might reduce the frequency of replication events compared to potato.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanisms such as polyploidization and region-specific gene duplication, including tandem repeats and segmental repeats, have been considered as important mechanisms for the expansion of plant gene families [ 29 , 30 ]. This study revealed the presence of homologous gene clusters and collinear gene pairs identified in both tobacco (1 homologous gene cluster and 6 collinear gene pairs) and potato (4 homologous gene clusters and 7 collinear gene pairs), indicating that replication events were the main source of DIR gene family expansion in these species [ 29 , 31 ]. It is worth noting that the incomplete genomic assembly of tobacco, with nearly half of the NtDIR genes located on scaffolds, might reduce the frequency of replication events compared to potato.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 75 tobacco seedlings were carefully selected and then inoculated with a highly virulent pathogenic strain of Ras that had been isolated by our laboratory [ 48 ]. Inoculation was performed by mechanically wounding the roots and followed by irrigation with 30 mL of Ras liquid with a concentration of 10 8 cfu/mL [ 31 ]. These plants were then cultivated in a high-temperature and high-humidity greenhouse (30℃, about 80% humidity, 12 h/d light).…”
Section: Methodsmentioning
confidence: 99%